Development of a Training Program for Upskilling Science Teachers’ Laboratory Competence - Cabacungan, Mark Vincent R.; Calzada, Marc Paul T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Science education in the Philippines is presently alarming due to the low achievement rating in various international assessments. This problem is rooted in the low utilization of laboratory-based instruction due to inadequate laboratory facilities and equip-ment. Hence, a descriptive-correlational research approach was conducted to determine the knowledge and skill competence of public-school teachers. Using a researcher-made survey ques-tionnaire, it was revealed that the respondents have very high knowledge and skill competence when it comes to laboratory instruction with a mean score of 4.08 apiece. Meanwhile, an R-value of 0.9121 was computed showing a positive relationship between knowledge and skill competence. The result shows that teachers are competent enough to perform lab-based activities; however, there is a need for them to undergo training and semi-nars due to the low utilization of lab activities. From here, a training program dubbed as SCILAW was formulated. Through this, teachers will be able to hone their knowledge and skills in using lab-based teaching approaches.